Gender and age differences in symptom distress and functional disability at 1 year after heart transplant surgery - Jalowiec, Anne (2010)
BACKGROUND: Symptoms and functional status are major concerns for heart transplant (HT) patients. OBJECTIVE: To examine gender and age differences in symptom distress and functional disability at 1 year after HT surgery. METHODS: The sample (N = 237) consisted of 44 females and 193 males, who were divided into younger (n = 66) and older (n = 171) groups with the breakpoint at age 50. Data from chart review and 2 questionnaires (HT Symptom Checklist and Sickness Impact Profile) were analyzed with chi square, t-tests, ANOVA, and MANOVA. RESULTS: Women reported worse symptom distress (overall, plus cardiovascular, gastro-intestinal, dermatologic symptoms) and more functional disability (overall, plus disability in ambulation, mobility, self-care, home management). Older patients reported more disability in ambulation and work. Gender by age interactions showed that older men reported worse genito-urinary symptoms and younger women reported worse dermatologic symptoms. CONCLUSION: There were more gender than age differences in symptoms and disability.